2021
DOI: 10.3390/cimb43030120
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Diabetic Nephropathy by Targeting Autophagy via Rapamycin or Fasting: Relation to Cell Apoptosis/Survival

Abstract: Autophagy has been demonstrated to have a beneficial effect on diabetic nephropathy (DN). Rapamycin, an inhibitor of mTOR, was shown to stimulate β-cell autophagy. However, its effects on preventing or ameliorating DN is unclear, and its effects are worth studying. As fasting is now an attractive protective strategy, we aim to compare its effect to rapamycin effects on pancreatic and renal cells. Twenty-eight adult male Wistar Albino rats were randomly divided into four groups, using streptozotocin (STZ) to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Thus, a calorie restriction regimen must be regarded as an effective therapeutic approach to inhibit diabetic nephropathy. Calorie restriction enhances renal impairment in type II diabetic Wistar fatty rats, and it repairs autophagy activity in their proximal tubular cells [ 147 ]. Therefore, an agent that can imitate caloric restriction might be a potential therapy for diabetic nephropathy by inducing autophagy in mammalian cells.…”
Section: Therapeutic Implications Of Programmed Cell Death In Diabeti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a calorie restriction regimen must be regarded as an effective therapeutic approach to inhibit diabetic nephropathy. Calorie restriction enhances renal impairment in type II diabetic Wistar fatty rats, and it repairs autophagy activity in their proximal tubular cells [ 147 ]. Therefore, an agent that can imitate caloric restriction might be a potential therapy for diabetic nephropathy by inducing autophagy in mammalian cells.…”
Section: Therapeutic Implications Of Programmed Cell Death In Diabeti...mentioning
confidence: 99%
“…Thus, rapamycin might be protective in diabetic nephropathy by activating autophagy. However, extreme mTORC1 prevention impairs podocyte function, suggesting that further investigation is required regarding the safety and effectiveness of mTORC1 prevention in patients with diabetic nephropathy [ 147 , 148 ].…”
Section: Therapeutic Implications Of Programmed Cell Death In Diabeti...mentioning
confidence: 99%
“…Moreover, IF also improved the peripheral and central changes induced by a high-fat diet by maintaining the balance of autophagy [ 90 ]. The direct evidence linking IF, autophagy, and DN was demonstrated by Gouda et al in an STZ-induced DN mice model, where apoptosis was increased, and autophagy was inhibited, while fasting restored renal autophagy, reduced apoptosis, and alleviated kidney injury [ 91 ] ( Figure 2 ). Although the molecular mechanism underlying autophagy activation by IF in DN remains to be studied further, it is confirmed that IF-mediated autophagy activation is an effective protective strategy against DN.…”
Section: Molecular Mechanism Of If Alleviation Of Dn Progressionmentioning
confidence: 99%